2020
DOI: 10.1007/s11258-020-01010-7
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen and phosphorus influence Acacia saligna invasiveness in the fynbos biome

Abstract: This study attempts to understand how invasive legumes such as Acacia saligna may compete with indigenous legumes such as Virgilia divaricata. The two species are trees with similar growth forms. We studied the competitive ability of invasive and indigenous seedlings under variations in soil phosphorus availability. South African fynbos vegetation is threatened by invasive Acacia. The indigenous tree legume, Virgilia, grows in similar phosphorus soil conditions as Acacia although there is a gap in the knowledg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 52 publications
1
4
0
Order By: Relevance
“…Forrester et al [106] also recorded high cycling of P in annual leaf litterfall production in an Acacia mearnsii plantation. The high addition of P in AMDF and P use efficiency indicates a high P demand, common in areas with N-fixing species [107]. Inagaki et al [26] found a positive correlation between the production of reproductive parts with soil P availability, consistent with our findings of high reproductive output in both Acacia-invaded habitats.…”
Section: Effects Of Acacia Invasion On Stand-level Nutrient Use Effic...supporting
confidence: 89%
“…Forrester et al [106] also recorded high cycling of P in annual leaf litterfall production in an Acacia mearnsii plantation. The high addition of P in AMDF and P use efficiency indicates a high P demand, common in areas with N-fixing species [107]. Inagaki et al [26] found a positive correlation between the production of reproductive parts with soil P availability, consistent with our findings of high reproductive output in both Acacia-invaded habitats.…”
Section: Effects Of Acacia Invasion On Stand-level Nutrient Use Effic...supporting
confidence: 89%
“…Simultaneously, NP15:2 may provide additional phosphorus to support RNA synthesis in introduced populations. This preference for phosphorus can aid in the maintenance of introduced plant mass and larger leaf area ( Rivas-Ubach et al 2012 ; Esterhuizen et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previously it was reported that invasive species are common in semi-arid areas because of their specific environmental needs, such as the amount of light they need [40]. Recent studies concluded that the high amounts of ecosystem disturbance occurring in all kinds of habitats, including riparian ecosystems, rural farmland, urban greenbelts, wetland ecosystems, and forest ecosystems, facilitated the invasion of new species [6,[41][42][43].…”
Section: Effect Of P Juliflora On the Associatedmentioning
confidence: 99%